ESTIMATION OF SEDIMENT VOLUME DURING WATER INTAKE FROM THE AMUDARYA RIVER TO PUMPING STATIONS (International Conference on Economics, Finance, Banking and Management, 2025)
The article examines methods for ensuring guaranteed water supply and investigates sedimentation processes in the main settling basin. Based on a comprehensive study of the water conveyance channel, recommendations were developed to improve its operation. The hydraulic and alluvial regimes of sediments in the water conveyance channel were analyzed, and the results were summarized. Furthermore, recommendations were proposed for organizing sediment removal operations and appropriately placing dredgers along the channel length. The placement of dredgers was performed considering the distribution of sediment volumes along the channel, as well as the type and operation mode of each dredger.